PENGARUH LITERASI MEDIA SOSIAL TERHADAP KESADARAN KRITIS MASYARAKAT UNTUK MENGHINDARI MODUS PENIPUAN ONLINE : Survei Pengguna Media Sosial Instagram Pada Mahasiswa Program Studi Ilmu Komunikasi UPN "Veteran" Jakarta - Juan Dwi Satya (2021)
The development of communication technology is increasingly growing rapidly. The communication media that is most widely used by many people is social media, one of which is Instagram. According to Napoleon Cat data, Instagram social media users in Indonesia as of November 2020 amounted to 81,770,000. Based on the number of social media users, Instagram is also followed by the amount of information received. In this study, researchers will conduct research on the effect of social media literacy on UPN "Veteran" Jakarta Communication Study Program students in an effort to avoid online fraud mode on Instagram social media. Researchers used James Potter's theory of media literacy to measure the effect of social media literacy on people's critical awareness. In this study, researchers used a quantitative approach by determining as many as 92 people who would be respondents to be researched. This study uses an explanative survey method, which can be said that there is a strong influence of 0.794 social media literacy on people's critical awareness to avoid online fraud mode. The results of testing the coefficient of determination showed the effect of Social Media Literacy on Community Critical Awareness of 63%, while the remaining 37% was caused by other factors not examined in this study. The results of hypothesis testing from this study obtained tcount of 12.406. So hereby H0's statement is rejected and H1 is accepted. This means that there is an influence of Social Media Literacy on Community Critical Awareness to avoid online fraud mode.